Transition-Metal-Free Enantioselective Reactions of Organomagnesium Reagents Mediated by Chiral Ligands - Guyon, Hélène; Boussonnière, Anne; Castanet, Anne-Sophie (Synthesis, 2018)
Organomagnesium reagents are among the most important reagents in organic chemistry because of their great utility in forming carbon–carbon bonds. Although most enantioselective reactions using these organometallics involve transmetalation, the past decade has witnessed impressive advances in direct chiral-ligand-mediated reactions of organomagnesiums. This short review presents an overview of these achievements in enantioselective nucleophilic additions and substitutions.1 Introduction2 Enantioselective Nucleophilic Additions2.1 Addition to C=O Bonds2.2 Addition to C=N Bonds2.3 Addition to C=C Bonds3 Enantioselective Substitution Reactions3.1 Sulfoxide–Magnesium Exchange3.2 Desymmetrization via Anhydride Opening3.3 Asymmetric Allylic Alkylation (AAA)4 Conclusion
Keywords: magnesium; Grignard reaction; asymmetric synthesis; enantioselectivity; ligands